2004
DOI: 10.1523/jneurosci.1275-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Role for Kv3 Voltage-Gated Potassium Channels in Starburst Amacrine Cell Signaling in Mouse Retina

Abstract: Direction-selective retinal ganglion cells show an increased activity evoked by light stimuli moving in the preferred direction. This selectivity is governed by direction-selective inhibition from starburst amacrine cells occurring during stimulus movement in the opposite or null direction. To understand the intrinsic membrane properties of starburst cells responsible for direction-selective GABA release, we performed whole-cell recordings from starburst cells in mouse retina. Voltage-clamp recordings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 55 publications
5
87
1
Order By: Relevance
“…Similar differential localization of GABA A receptors has been described in hippocampal pyramidal cells (Nusser et al, 1996a) and cerebellar granule cells (Nusser et al, 1996b). In addition to receptors, it has recently been shown that mouse starburst amacrine cells express strongly Kv3 voltage-gated potassium channels on their cell bodies and proximal dendrites, with the intermediate and distal dendrites showing significantly lower levels of expression (Ozaita et al, 2004). Also, on rabbit starburst amacrine cells, there is evidence that chloride gradients generated by two different cation-chloride cotransporters contribute to differences in biophysical properties seen on the proximal and distal dendrites of these cells (Gavrikov et al, 2003).…”
Section: Functional Compartmentalization On Individual Neuronssupporting
confidence: 65%
“…Similar differential localization of GABA A receptors has been described in hippocampal pyramidal cells (Nusser et al, 1996a) and cerebellar granule cells (Nusser et al, 1996b). In addition to receptors, it has recently been shown that mouse starburst amacrine cells express strongly Kv3 voltage-gated potassium channels on their cell bodies and proximal dendrites, with the intermediate and distal dendrites showing significantly lower levels of expression (Ozaita et al, 2004). Also, on rabbit starburst amacrine cells, there is evidence that chloride gradients generated by two different cation-chloride cotransporters contribute to differences in biophysical properties seen on the proximal and distal dendrites of these cells (Gavrikov et al, 2003).…”
Section: Functional Compartmentalization On Individual Neuronssupporting
confidence: 65%
“…The large TEA-induced enhancement of evoked GABA release is absent in Kv3.1/Kv3.2 double knock-out mice To obtain more direct evidence that the effect of TEA on spikeevoked GABA release is mainly attributable to blockade of presynaptic channels containing Kv3.1 and Kv3.2 proteins, we performed experiments using Kv3.1/Kv3.2 double knock-out (DKO) mice (Ozaita et al, 2004). In slices prepared from DKO mice, the large TEA-induced enhancement of eIPSCs seen in wild-type animals was absent, and TEA produced only a small increase in the eIPSC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In neocortex, thalamus, hippocampus, and striatum, Kv3-type channels are found in GABAergic cells (mostly interneurons) that also express the calcium-binding protein parvalbumin (PV), a marker for fastspiking neurons. The genetic elimination of Kv3.1 or Kv3.3 increases AP duration, reduces high-frequency firing, and affects synaptic transmission of neurons in several brain nuclei (Lau et al, 2000;Porcello et al, 2002;Macica et al, 2003;Matsukawa et al, 2003;McMahon et al, 2004;Ozaita et al, 2004). The coexpression of Kv3.1 and Kv3.3 channel subunits in several brain regions suggests that functional redundancy among these subunits may exist.…”
Section: Introductionmentioning
confidence: 99%